2017
DOI: 10.1186/s13293-017-0137-7
|View full text |Cite
|
Sign up to set email alerts
|

Difference in clinical presentation between women and men in incident primary Sjögren’s syndrome

Abstract: BackgroundA more severe disease phenotype has been reported in men compared to women in several rheumatic diseases. However, studies have not conclusively established sex-related clinical features in primary Sjögren’s syndrome (pSS). In this study, we therefore investigated the clinical presentation of pSS in women and men at diagnosis.MethodsIncident, treatment naïve patients (n = 199) during a 5-year period in a specified area were prospectively included and examined for items of classification criteria for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 45 publications
4
44
1
3
Order By: Relevance
“…Finally, a worse outcome was associated to the male gender in the present study. This observation is consistent with recent published work on sex difference in two independent cohorts of incident primary SS, which demonstrated that the presence and number of extraglandular manifestations are significantly more frequent among men than in women with pSS, (29). This study then confirms that pSS males may suffer from a more severe form of disease.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, a worse outcome was associated to the male gender in the present study. This observation is consistent with recent published work on sex difference in two independent cohorts of incident primary SS, which demonstrated that the presence and number of extraglandular manifestations are significantly more frequent among men than in women with pSS, (29). This study then confirms that pSS males may suffer from a more severe form of disease.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, our population was mainly composed of women (93%), as observed in an independent French cohort of pSS (ASSESS) [27]. In other cohorts, men were more represented, which could partly explain the low vaccination coverage in our population [28], as men usually experience more severe disease with shorter follow-up intervals. It is known that patients who are monitored closely have better vaccination coverage than patients who are managed with no specific instructions [29].…”
Section: Discussionmentioning
confidence: 83%
“…Missing data may have arisen based on patients’ willingness or ability to participate fully each day, despite the 2-week period given for responses and multiple probes by a moderator. Males represented only 6% of the study population; however, it is estimated that Sjögren’s syndrome is 9–14 times more prevalent in females than males [ 26 ]. Finally, disease information was provided by patients and not physicians, with no further opportunity to investigate the pSS diagnosis, for instance, in terms of specific extra-glandular manifestations.…”
Section: Discussionmentioning
confidence: 99%